2020
DOI: 10.1080/17430437.2020.1804109
|View full text |Cite
|
Sign up to set email alerts
|

Signaling soft power through medal success: China as an example

Abstract: Using China as an example, this study seeks to examine whether and how a country's elite sport success would affect its soft power from international audience's perspective. Data were collected from residents of Paris through self-completion structured questionnaires. While the results of the study showed varied improvement on three national image dimensions, respondents' perception about China's government and policy worsened. Drawing on costly signaling theory and attribution theory, Olympic involvement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…The growth of the experience economy in China has been reflected in the growth of its tourism industry, which was boosted significantly, along with its prominence as a destination in in the international tourism market with an improved destination image, following the hosting of three mega-events: The 2008 Olympic and Paralympic Games in Beijing, the 2010 World Expo in Shanghai, the 2010 Guangzhou Asian Games (Leung et al, 2014), and the 2016 G20 in Hangzhou. Hosting these events, and bidding to host future events including the Winter Olympics and the Asian Games, both in 2022, indicates that the Chinese government has also come to recognize the power of events for achieving their goals in urban and foreign policy through a "soft power" strategy that has long been used elsewhere (Grix et al, 2019;Liu, 2020).…”
Section: Events Management In the "Chinese Century"mentioning
confidence: 99%
“…The growth of the experience economy in China has been reflected in the growth of its tourism industry, which was boosted significantly, along with its prominence as a destination in in the international tourism market with an improved destination image, following the hosting of three mega-events: The 2008 Olympic and Paralympic Games in Beijing, the 2010 World Expo in Shanghai, the 2010 Guangzhou Asian Games (Leung et al, 2014), and the 2016 G20 in Hangzhou. Hosting these events, and bidding to host future events including the Winter Olympics and the Asian Games, both in 2022, indicates that the Chinese government has also come to recognize the power of events for achieving their goals in urban and foreign policy through a "soft power" strategy that has long been used elsewhere (Grix et al, 2019;Liu, 2020).…”
Section: Events Management In the "Chinese Century"mentioning
confidence: 99%
“…In relation to international prestige, some researchers worked on this tangible effect and soft power. Liu (2020) examines whether and how a country"s elite sport success would affect its soft power from an international audience"s perspective. The results not only provided empirical evidence of whether Olympic achievement would have affected a country"s soft power but offered insights on the mechanisms at work behind that effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, there has been an increasing attention toward elite sports. States intervene increasingly in the financing and organization of Olympic elite sport Carmichael 2012, Haut et al 2017), and governments frequently are motivated by a quest for international image and prestige (Hubbert 2013, Liu 2020, Park et al 2012, Silk 2013, Tan and Houlihan 2013. In particular, having high prestige levels can be considered as a source of states" soft power through which states can convert resources into policy outcomes (Grix 2014, Nye 2008.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Zheng et al [13] concluded that the PRC enjoys a well-organized and stratified three-level training system (see Figure 1). Officially established in 1963, when the then Sports Ministry promulgated the Regulations of Outstanding Athletes and Teams [12] (p. 516), it was recognized as one of the most effective training systems in the world and perceived as the core of Juguo Tizhi (precisely and explicitly interpreted as "whole country support for elite sport system"), underpinning the PRC's continuous presence as one of the three best-performing nations at the Summer Olympics [5,10,17]. Regarding the governance structure, as depicted in Figure 1, provincial sports bureaus (PSBs) run provincial elite teams on behalf of both the General Administration of Sport (GAS), in the vertical direction, and the respective provincial governments (PGs), horizontally [18] (p. 688).…”
Section: Elite Sport Training In China and An Integrative Model Of Organizational Change In Sport 21 Institutional Analyses On Chinese Elmentioning
confidence: 99%